A Short Proof of the Characterization of Model Sets by Almost Automorphy - Aujogue-, J (CANADIAN MATHEMATICAL SOC, 2018)
The aim of this note is to provide a conceptually simple demonstration of the fact that repetitive model sets are characterized as the repetitive Meyer sets with an almost automorphic associated dynamical system.